g-C3N4/MWCNT nanocomposite based electrochemical sensor for hydrogen peroxide detection - Shukla S.; Prakash Ojha R.; Ji G.; Prakash R. (My University, 2025)
Hydrogen peroxide (H2O2) is an important chemical used in various industries like pharmaceutical, food, textile, material science, and cosmetics for various applications such as synthesis, medicine, disinfectant, bleaching, etc. The limited use is beneficial; however, the high level of H2O2 can create serious health issues for humans. Hence, precise and early detection is necessary. The present work reports electrochemical sensing of H2O2 by using graphitic carbon nitride multi-walled carbon nanotubes (g-C3N4/MWCNT) nanocomposite modified electrode. The formation of nanocomposite has been confirmed by X-ray diffraction (XRD) technique, scanning electron microscopy (SEM), and energy dispersive X-ray analysis (EDAX). The H2O2 sensing is done by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and differential pulse voltammetry (DPV). The results of all the techniques used have shown that g-C3N4/MWCNT nanocomposite does better H2O2 sensing (more sensitive) than g-C3N4 and MWCNT. To analyze the sensing kinetics, the DPV response is plotted against H2O2 concentration. The linear graph is acknowledged, which shows its potential for fabricating the sensor. © 2022